Implementation of Ministry of Health Regulation No. 2/2025 on Reproductive Health - Samara Naswa; Dewi Fitriana Sari; Tri Utami Fitria; Lisbet Natalia Simamora; Magda Doria; Winnie Tunggal Mutika (Universitas Mulawarman, 2026)
Ministry of Health Regulation Number 2 of 2025 on Reproductive Health is a strategic regulation aimed at ensuring the fulfillment of reproductive health rights for all individuals, including adolescents, couples of reproductive age, pregnant and breastfeeding women, the elderly, and persons with disabilities. This study employs a literature review method to examine the implementation of the regulation based on various previous studies discussing programs, challenges, and the impact of reproductive health services in Indonesia. The findings indicate that although the regulation provides a comprehensive framework for health service providers, its implementation remains inconsistent across regions. Major challenges include the limited availability of trained human resources, inadequate infrastructure, and low reproductive health literacy among the public. On the other hand, several best practices have been identified, such as school-based health education, the use of digital media for public outreach, and youth empowerment programs. Based on the reviewed literature, this study recommends more integrated, evidence-based implementation strategies, enhanced capacity-building for health workers, and stronger cross-sectoral collaboration to achieve inclusive and equitable reproductive health services